FINTECH SYARIAH DAN PERLINDUNGAN KONSUMEN MUSLIM: MENATA ULANG KERANGKA HUKUM BISNIS DI TENGAH DISRUPSI GLOBAL DI KABUPATEN PINRANG - Reni Anggreni; Nur Afiat Agus; Zainal Said; Hannani Hannani (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The development of Islamic financial technology (fintech) has accelerated the transformation of financial services by providing faster, more accessible, and inclusive financial solutions for Muslim communities. However, this advancement has also generated challenges related to consumer protection, personal data security, information transparency, and regulatory effectiveness amid digital disruption. This study aims to analyze the practices of Islamic fintech utilization, the protection of Muslim consumers, the effectiveness of the existing business legal framework, and to formulate a reconstructed legal framework for Islamic fintech in Pinrang Regency. This research employed a qualitative approach using field research methods through in-depth interviews, observations, and documentation. The informants consisted of Islamic fintech users, micro and small business owners, academics, religious leaders, and Islamic finance practitioners. The findings reveal that Islamic fintech is widely accepted due to its accessibility and efficiency in financial services. Nevertheless, consumer protection remains challenged by low Islamic financial literacy, limited understanding of sharia contracts, concerns regarding personal data security, and inadequate awareness of dispute resolution mechanisms. The study also identifies a regulatory gap caused by the rapid pace of technological innovation compared to legal and regulatory developments. Therefore, this research proposes a reconstructed Islamic fintech business law framework based on adaptive regulation, literacy enhancement, digital data protection, and the integration of maqashid al-shariah principles as the foundation of Muslim consumer protection. This framework is expected to strengthen consumer protection while supporting the sustainable development of Islamic fintech. Keywords : Islamic fintech; Consumer protection; Business law; Maqashid alshariah; Digital disruption.